Model-Model Pendidikan Karakter di Sekolah - Hasanah, Uswatun (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2016)
Currently, there is no doubt that the emergence of various social phenomena is very worrying in many cases form; violence and unrest and moral decadence that befell this nation. The character  of the  young generation  is already  at an alarming point. The morality of this nation has  been separated  from the  norm,  ethical,  religious and  noble culture.  Damage to morale among  students and  youth.  It is  characterized by  the rise of casual sex, drug abuse, trafficking in photos and porn video, and fights among students and youth.Based on the results of research conducted by the Institute for the Study of Love and Humanity as  well as  Business  Training and  Humanities  (LSCK  PUSBIH),  involving  1,666 respondents in large cities, for example; Medan, Jakarta, Bandung, Yogyakarta, and Surabaya. Teen respondents  claimed to have free  sex is  very high,  even exceeding  50%.  In addition, according to  the  Centers for  Disease  Control  Jakarta  Social  Disorder,  elementary school, junior high  and high school,  which involved  brawl reached  0.8%,  or approximately  1,318 students (1,645,835), as well as victims of drugs 3.9%. And, even more surprising, for the city of Yogyakarta, about 97.05%, free sex. The facts demonstrate how ironic condition of today's teenagers.Here,  the importance of character education in schools internalization intensively by example,  wisdom, and  unity both  intra and extra-curricular  programs,  as a  solid foundation that will benefit future students. Character development is largely forgotten by the school, has been too  fascinated with  academic targets,  dianak favoring  the intellectual,  emotional and spiritual intelligence while marginalized. It can be concluded that the character of the values of human behavior associated with the Almighty God, ourselves, our fellow human beings, the environment, and nationality embodied in thoughts, attitudes, feelings, words, and actions based on religious norms, laws, etiquette, culture, and customs.